The answer is: " 2" .
___________________________________________
Answer: " f[g(0)] = 2 " .
___________________________________________
Step-by-step explanation:
___________________________________________
Given: " f(x) = 3x + 5" ; and: " g(x) =x − 1" ;
Question to solve: "What is: f[g(0)] ? " ;
__________________________________________
What is "ef" of "gee" of "zero"?
__________________________________________
Let us begin by finding "g(0)" ;
Given: " g(x) = x − 1 " ;
To find: " g(0) " ; we plug in "0" for all values of "x" ; and solve; as follows:
→ " g(0) = 0 − 1 = -1 " ;
→ So; " g(0) = -1 " .
_______________________________________________________
We are asked to find: " f[g(0)] " ;
which is: " f(-1) " .
Given: "f(x) = 3x + 5" ;
→ To find " f(-1)" ; we plug in: "-1" for all values of "x" ; and solve; as follows:
→ " f(-1) = 3(-1) + 5 = -3 + 5 = 2 .
____________________________________________________
The answer is: " 2" .
____________________________________________________
Answer: " f[g(0)] = 2 " .
____________________________________________________